Evaluation of hydrogen storage performance of ZrTiVNiCrFe in electrochemical and gas-solid reactions. (14th February 2020) - Zadorozhnyy, V.; Sarac, B.; Berdonosova, E.; Karazehir, T.; Lassnig, A.; Gammer, C.; Zadorozhnyy, M.; Ketov, S.; Klyamkin, S.; Eckert, J.
Abstract: In the present study, the hydrogen storage performance of multi-principal-component ZrTiVNiCrFe alloy produced through rapid solidification has been examined by electrochemical methods and gas-solid reactions. XRD and EBSD analyses reveal the hexagonal Laves phase structure (type C14) with average grain size of 300 nm and root-mean-square microstrain of 0.19%. Cyclic voltammetry and electrochemical impedance spectroscopy analyses in the hydrogen sorption/desorption region give insight to the sorption/desorption kinetics and the change in the desorption charge in terms of the applied potential. The pressure-composition isotherms measured in course of gas-solid reaction confirm the hydrogen storage capacity reaching 1.6 wt% at the first hydrogenation at room temperature, then reducing to 1.3–1.4% during subsequent cycling. According to the calorimetric titration study, there is a significant hysteresis primarily caused by the non-equilibrium character of the hydrogenation process. Highlights: Single phase ZrTiVNiCrFe has been synthesized by melt spinning. Reversible hydrogenation was confirmed by gas-solid and electrochemical methods. Maximum hydrogen capacity at room temperature reaches 1.6 wt%. Hydrogen desorption enthalpy of 38 kJ/mol H2 was evaluated from calorimetric measurements.